SEASONAL VARIABILITY OF NUTRIENTS IN THE RIVER VORSKLA - Авраменко, Н. І. (Scientific Progress & Innovations, 2014)
Specified is the main factors that have the greatest impact on the seasonal variability of nutrients in the river Vorskla. Found that an important role is played by the natural cyclical fluctuations in water flow and its regulation of . Specified is a direct relationship between the vital functions of aquatic and seasonal content of nutrients in water bodies . The results of research on the impact of hydrobiological ( photosynthetic ) processes and biological factors on fluctuations in the values ​​of nutrient content . Emphasized that the levels of nutrients limiting the development of biological processes in the water. Determined that the variability of nutrients in river water has a distinctly seasonal. The dependence on the magnitude of water runoff and the development of hydrobiological processes.